The relationship between ventilatory and lactate thresholds in boys and men - Anderson, C. S.; Mahon, A. D. (Research in Sports Medicine, 2007)
The relationship between ventilatory (VT) and lactate threshold (LT) in 8 boys (11.1 ± 0.7 yrs) and 9 men (24.0 ± 3.3 yrs) with similar peak VO2 levels was assessed. Percent peak VO2 at VT and LT were higher (P < 0.05) in the boys (67.9 ± 2.6% and 63.9 ± 5.0%, respectively) compared with men (59.0 ± 3.2% and 54.8 ± 2.7%, respectively). VO2 (mL·kg-1·min-1) at VT was higher (P < 0.05) and at LT tended to be higher in boys. Correlations between VT and LT were r = 0.95 for VO2 (mL·kg-1·min-1) and r = 0.82 for % peak VO2 (P < 0.05) in boys and r = 0.87 (P < 0.05) and r = 0.60 (P > 0.05), respectively, in men. The mechanisms mediating VT and LT in children are not established fully and warrant further study.